Assessment of childhood vaccination hesitancy among syrian parents under temporary protection - Elif Nur Kocak; Betül Zehra Pirdal; Servet Yüce; Muhammed Atak; Hatice Kocak Alkan; Mihriban Aksoy; Osman Faruk Bayramlar (BMC Public Health)
Abstract Background and Aim Vaccination programs become increasingly crucial during migratory movements driven by conflict and other disruptions. This study aims to determine the prevalence of childhood vaccination hesitancy among Syrian parents under temporary protection and identify areas for targeted interventions. Method A total of 227 Syrian parents attending three Immigrant Health Centers in Sultangazi were assessed using the Arabic version of the Parent Attitude about Childhood Vaccines (PACV) survey, conducted between October and December 2023. Results The prevalence of vaccine hesitancy among these parents was found to be 10.6%. An inverse correlation was observed between maternal education level and vaccine hesitancy, indicating that higher education levels were associated with lower levels of hesitancy. Conclusion The observed rate of vaccine hesitancy among Syrian parents under temporary protection underscores the urgent need for targeted interventions. Tailored vaccination strategies for immigrant populations are essential to improve immunization rates and ensure the health and well-being of these communities.